Mischaracterization: Players' Lack Of Media Literacy Regarding The Story And Narratives Of Genshin Impact Characters - Syahla Almalika Nugraha; Siti Khumayah; Dian Andriany (ann4publisher@gmail.com, 2026)
Background. The evolution of video games as a complex narrative medium has raised new challenges regarding players’ interpretation of characters. Aims. This study examines the phenomenon of “mischaracterization”—that is, errors in understanding and representing characters resulting from a partial or distorted reading of the narrative—within the player community of Genshin Impact, an action-RPG developed by HoYoverse that delivers its story episodically through periodic updates. Methods. Using a descriptive qualitative approach and Potter’s (2021) Media Literacy Theory framework—which encompasses the dimensions of access, analysis, evaluation, creation, and self-awareness (personal locus)—this study collected data from an online questionnaire administered to 44 active players. Result. The results reveal patterns of imbalance in media literacy competencies: respondents demonstrated relatively high abilities in accessing information and awareness of the industry’s commercial motives, yet their conceptual analysis skills (distinguishing between canon and fanon) and reflective awareness of personal bias were low. These findings reinforce the view that media literacy is multidimensional and cannot be generalized based on a single competency dimension alone. Conclusion. This study also highlights that mischaracterization is not merely a matter of individual cognitive deficits but is also influenced by the episodic narrative structure of the games themselves, as well as the pressure for convergence of opinion within the participatory culture of online communities.